PENCAHAYAAN KOMBINASI PADA LABORATORIUM TEKNIK ELEKTRO POLITEKNIK NEGERI JAKARTA - Alfiana, Muhamad Ega; Alfares, Muhammad Aji; Nurwidyaningrum, Dyah; Wulandari, Linda Sari (Politeknik Negeri Jakarta, 2020)
ABSTRACTLighting in the Electrical Engineering Laboratory of the Jakarta State Polytechnic (PNJ) is one-factor supporting student practice activities from 07.30 - 16.00 WIB. The observation indicated that the PNJ Electrical Engineering laboratory's lighting undistributed evenly, even though more comprehensive lighting is needed to run well. The purpose of this study is to analyze the suitability of lighting in the Electrical Engineering laboratory with the minimum standard of SNI 03-6575-2001 concerning Procedures for Designing Artificial Lighting Systems in Buildings. The method used in this research is to compare the measurement results against the SNI 03-6575-2001 standard. Researchers took measurements in the Safety and Electrical Machinery laboratory room, Analog laboratory 1 and Digital laboratory 2, Department of Electrical Engineering, State Polytechnic of Jakarta. Analysis of the percentage suitability of combination light in the Safety and Electrical Machinery laboratory in general, namely 70.67%. Based on the measurement results, the suitability of lighting in the Department of Electrical Engineering laboratory, State Polytechnic of Jakarta, is already following SNI's minimum lighting level.Keywords: Electrical engineering laboratory; Artificial lighting; Lighting in the laboratoryABSTRAKPencahayaan di laboratorium Teknik Elektro Politeknik Negeri Jakarta (PNJ) adalah salah satu faktor penunjang kegiatan praktik mahasiswa dari pukul 07.30 – 16.00 WIB. Dari hasil observasi diketahui pencahayaan di laboratorium Teknik Elektro PNJ kurang merata, padahal dibutuhkan pencahayaan yang lebih menyeluruh agar kegiatan dapat berjalan dengan baik. Tujuan penelitian ini untuk menganalisis kesesuaian pencahayaan di laboratorium Teknik Elektro dengan standar minimum SNI 03-6575-2001 tentang Tata Cara Perancangan Sistem Pencahayaan Buatan pada Bangunan Gedung. Metode yang digunakan dalam penelitian ini adalah dengan membandingkan hasil pengukuran terhadap standar SNI 03-6575-2001. Peneliti melakukan pengukuran pada ruangan laboratorium Pengaman dan Mesin Listrik; laboratorium Analog 1 dan laboratorium Digital 2 Jurusan Teknik Elektro Politeknik Negeri Jakarta. Analisis persentase kesesuaian cahaya kombinasi pada laboratorium Pengaman dan Mesin Listrik secara umum, yaitu 70,67%. Berdasarkan hasil pengukuran, kesesuaian pencahayaan di laboratorium Jurusan Teknik Elektro Politeknik Negeri Jakarta sudah sesuai dengan tingkat pencahayaan minimum yang direkomendasikan SNI.Kata Kunci : Laboratorium teknik elektro; Pencahayaan buatan; Pencahayaan di laboratorium